Analysis Welding Types Pipe Fabrication Process in Missile Fast Attack Boat Construction - Sunarso Sugeng; Samuel Febriary Khristyson (Engineering And Technology Journal, 2024)
The equipment in the piping system consists of pipes, valves, flanges, filters, fittings, pumps, and others. The installation schedule for this piping system begins after the connection between blocks. Pipes as part of a ship's system have several steps in their installation procedure, one of which is welding. Welding on pipes is carried out by professional welders who have met more complex competency requirements than welders in general, such as flat position welders, vertical welders, or overhead welders. The purpose of this study was to determine the welding process and types of welding in pipe fabrication for the construction of the Missile Fast Attack Boat. Result comparison between the diameters of the welded pipes, the greater the value of the welding volume formed. The largest volume is 426 mm3, with a pipe length for the fabrication process of 4,3 m. On the other hand, the shortest fabrication is for welding pipes with a diameter of 2,5 m, which has a volume of 127 mm3. While the welding process using GTAW / Gas Tungsten Arc Welding (TIG) is very appropriate for welding in small areas and thin pipes. The TIG welding process has an average volume of below 150 mm3.